Способ электродуговой сварки с короткими замыканиями дугового промежутка и устройство для его осуществления - Князьков А. Ф. Анатолий Фёдорович; Мазель А. Г.; Дедюх Р. И. Ростислав Иванович; Сараев Ю. Н. Юрий Николаевич; Азаров Н. А. Николай Антонович
опубл. 1985, в Б. И. № 15